Lesson plan converter using optical character recognition integrated with Google Calendar / Idris Ishak - Ishak, Idris (2017)
Universiti Teknologi Mara (UiTM) adopts outcome based learning (OBE) and student centered learning (SCL) in their education program. These practices have been supported with the use of course information which contains lesson plan scheduling. Unfortunately, keeping up with learning progresses that was planned in the lesson plan is hard due to the fact that the information is presented in either paper-based or digital document. Paper-based documents are vulnerable and can easily get lost while digital documents are hard to be viewed frequently. The information in the lesson plan schedule can be well-managed and easy to be reviewed if it were to be stored in a digital calendar. By utilizing optical character recognition (OCR) the process of transferring information to a digital calendar can be simplified. This system development project adapts the iterative software development methodology and aims to assist students of Universiti Teknologi Mara Malaysia to generate digital calendar entries of their 14-week lesson activities using information provided in course information document so that they can be notified of important dates through their mobile devices or personal computers. With the integration with Google Calendar system, this feat can be achieved.